The Use of Academic Libraries in the Digital Age: What the Numbers Say - Barclay, Donald A. (International Higher Education, 2017)
Given the early twenty-first century’s wealth of information, it is a fair question to ask: “Are we approaching a time when academic libraries will no longer be necessary?” According to academic library usage data, the answer to this question is clearly “No.” While over the last ten to twenty years the number of books borrowed from U.S. academic libraries has plummeted, the number of people setting foot in those same libraries has significantly increased. And although longitudinal data for the use of non-U.S. libraries is hard to come by, a small sampling of academic libraries outside of the U.S. reflects a similar trend of fewer books borrowed coupled with more visits. The paper concludes by suggestions reasons for why students are making increased use of academic library spaces in the Digital Age.